Konsep al-Sahаbah dalam karya-karya Syiah berbahasa Melayu: Analisis menurut perspektif Ahl al-Sunnah wa al-Jamа‘ah / Mohd Aizam Mas’od - Mohd Aizam , Mas’od (2018)
The Concept of al-Sahаbah in Malay Language Syiah Works: An Analysis Based on the Perspective of Ahl al-Sunnah wa al-Jama‘ah, is the title of the study with the primary objective of identifying the foundations of Syiah thought on the concept of companions in some Malay language Syiah works and its judgement based on the thought of Ahl al-Sunnah wa al-Jama'ah. The study contains five chapters. The introduction, presenting the background, objectives, scope, highlight of previous studies and methodology used. The second chapter discusses Syiah in Malaysia and the introduction of selected Malay language Syiah works. The third chapter presents the fundamentals of Syiah thought on the concept of companions in selected Malay language Syiah works based on identified themes. The fourth chapter analyses and judges Syiah thought in these works according to the perspective of Ahl al-Sunnah wa al-Jama'ah. The fifth chapter brings about the conclusion of the study. In general, this study is based on a qualitative study concept driven by two methods of research namely the data collection and analysis methods. In order to analyse data, three subapplications were used, namely inductive, deductive and comparative methods. The study concludes that the foundations of the thought regarding the concept of the companions contained in the selected Malay language Syiah works are in accordance with the original Syiah Imamiyyah Ithna 'Ashariyyah. It begins with the rejection of the legitimacy of the term al-sahаbah (companion) in terms of syarak and ends with the denial of the authenticity of Ahl al-Sunnah wa al-Jama'ah. The findings show the flaws of Syiah thought and the importance of exposing such flaws based on the perspective of Ahl al-Sunnah wa al-Jama’ah.